Islamic Corporate Philanthropy in Islamic Banking: Implementation of Zakat Regulation and Sharia Compliance in Indonesia - Ely Masykuroh; Niswatul Hidayati; Yutisa Tri Cahyani (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to provide empirical evidence on the implementation of zakat management compliance and the influence of sharia corporate philanthropy on the performance of sharia commercial banks in Indonesia. This study uses a mixed method, combining quantitative and qualitative approaches. The collected data were then analyzed quantitatively using descriptive or inferential statistics. The research sample consisted of 12 Islamic banks registered with the OJK, and the secondary data for this study were taken from audited and published annual reports from 2017 to 2023. The data analysis technique used regression and legal interpretation analysis. The results of the study indicate that there is a significant influence of ICP performance and Islamic banks, and that there are examples of banking compliance with applicable laws. The contribution of this study lies in providing empirical evidence that compliance with zakat regulations and the implementation of Islamic corporate philanthropy have a positive impact on the performance of Islamic banking institutions. This study reinforces the argument that zakat is not only a moral or spiritual obligation, but also a strategic instrument in sustainable corporate governance. In addition, this research provides important input for regulators, banking practitioners, and zakat authorities in formulating more integrative and applicable policies, so as to optimize the potential of national zakat through synergy between regulations, institutions, and sharia corporate awareness.